Giant BCC of the scalp after telmisartan/amlodipine: potential role of nitrosamine contamination as main cause for skin cancer development - Georgi Tchernev; Simona Kordeva (Sociedade Portuguesa de Dermatologia e Venereologia, 2023)
The problem of drug-induced cancers, and in particular skin cancers after intake of various antihypertensive drugs, is increasing, but at the same time is gaining some clarity. In addition to melanocytic cancers, development of keratinocytic cancers is increased after the administration of sartans. It is believed that the procarcinogenic potential of the medication could be due to contamination of tablets with nitrosamines, which are known as mutagens. Regardless of the presence of angiotensin receptors in the skin and tumor tissue, the pharmacologic influence of the sartan is considered to be secondary and insignificant in relation to the processes of carcinogenesis. In certain cases, this influence is even defined as an antitumorous effect. We present a female patient who had been taking telmisartan/amlodipine 80/5 mg daily for 9 years and, after 4-5 years, developed a scalp tumor, confirmed histopathologically as a basal cell carcinoma (BCC) and treated successfully by surgical excision. The discussion is mainly focused on the potential role of nitrosamines as a new key player in the pathogenesis of keratinocytic cancers and BCC in particular.